Clinical Evaluation of the Hip With Focus on Assessment of Hip Instability - Elizabeth H. G. Turner MD; Lauren E. Watchmaker BA; Andrea M. Spiker MD (SAGE Publishing, 2022)
Background: Hip instability is a challenging clinical diagnosis, which often overlaps with the presentation of hip impingement and/or hip dysplasia. Many factors contribute to hip instability, including acetabular undercoverage, femoroacetabular-impingement-induced instability, and soft tissue laxity. It can cause significant pain and disability, either as a primary pathology or as a complication of surgery and if untreated can ultimately lead to early osteoarthritis. Indications: Hip dysplasia is often diagnosed with an anterior-posterior pelvic radiograph. The literature has supported a normal lateral center edge angle (LCEA) as ≥25°, borderline dysplasia an LCEA of 18° to 25°, and an LCEA <18° as true dysplasia, though some authors will diagnose borderline dysplasia as an LCEA of 20° to 25° and true dysplasia as an LCEA <20°. In addition, there are many radiographic measurements that have been described to aid in the diagnosis of hip instability beyond LCEA, including the acetabular inclination (or Tönnis angle), the femoro-epiphyseal acetabular roof (FEAR) index, and the cliff sign. Technique Description: Hip instability can be present even in the absence of radiographic findings, and many with insufficient coverage of the femoral head do not meet the radiographic definition of dysplasia. For this reason, it is important to have an understanding of the clinical assessment that may aid in the diagnosis of hip instability. Here, we present our preferred technique for clinical examination of the hip, focusing on the assessment of hip instability. Results: While no one maneuver is sufficient to diagnose hip instability, incorporation of multiple examinations in conjunction with radiographs can help to properly diagnose the presence of hip instability. Discussion/Conclusion: Hip instability is a challenging clinical diagnosis, and many examination maneuvers have been described to assess for hip instability. In this technical note, we describe our preferred technique for clinical examination of the hip, focusing on the assessment of hip instability.